Prospects of pulsed current arc welding on aerospace grade Hastelloy X. (August 2021) - Sathishkumar, M; Manikandan, M; Arivazhagan, N
The conventional constant current arc welding of Hastelloy X (Ni-Cr-Fe-Mo) leads to the solidification and liquation cracks in the weldment. The higher heat supplied in constant current weldment develops the secondary carbide precipitates. It promotes the development of hot cracks in the weldment. In this study, joining of Hastelloy X plates was carried out by constant current gas tungsten arc welding (GTAW) and pulsed current gas tungsten arc welding (PCGTAW) with C263 filler wire. The result discovered that no hot cracks were formed in the weldment. In constant current mode, Cr-rich and Mo-rich Cr23 C6 (M23 C6 ), Fe2 MoC, Fe3 Mo3 C (M6 C), and Cr2 Ti precipitates were observed. Whereas, in pulsed current mode, Ni3 (Al, Ti), Ni3 Ti, Co3 Ti, Cr2 Ti precipitates are found due to the segregation of Co, Al, and Ti. No Cr-rich and Mo-rich carbide phases identified in pulsed current weldment due to rapid cooling rate and higher thermal gradient observed during solidification. The tensile results revealed that 8.23% increase in the ultimate tensile strength and a 29.62% increase in elongation of pulsed current mode welding compared to constant current welding. Further, the microhardness and impact toughness of PCGTAW is 3.32% and 5.45% higher than GTAW, respectively. In pulsed current welding, better mechanical properties were identified compared to constant current welding. The nonappearance of Cr and Mo-rich phases and refined microstructure in the weldment are the main reason for better strength.